Immune Checkpoint Inhibitor-Induced Diabetic Ketoacidosis: A Report of Four Cases and Literature Review - Hong, A Ram; Yoon, Jee Hee; Kim, Hee Kyung; Kang, Ho-Cheol (Frontiers in Endocrinology, 2020)
Immune checkpoint inhibitors (ICIs) have been widely used in the treatment of various types of cancers worldwide. Although ICI-related autoimmune diabetes is a rare complication, it can be associated with a life-threatening condition, diabetic ketoacidosis (DKA). Here, we report the cases of four patients who presented with ICI-induced DKA in a tertiary center in Korea. Three patients were newly diagnosed with type 1 diabetes, and one patient was known to have a history of type 2 diabetes. All DKA cases were due to programmed cell death protein-1 (PD-1) or its ligand inhibitors (PD-L1). The mean age of the patients was 71.5 years, and the mean time for diagnosing the onset of DKA after starting ICIs was 15.8 weeks. Glutamic acid decarboxylase antibodies were positive in one patient (25%) who already had been treated with type 2 diabetes. All four patients showed improved antitumor responses after ICI therapy and are currently receiving insulin treatment for glycemic control, regardless of their continuation of ICIs. As there have been no practically available predictive biomarkers for the diagnosis of DKA or type 1 diabetes thus far, close monitoring of blood glucose levels is required in all patients receiving ICIs.